Integrated modeling framework to quantify the coastal protection services supplied by vegetation. Issue 1 (28th January 2015) - Guannel, Greg; Ruggiero, Peter; Faries, Joe; Arkema, Katie; Pinsky, Malin; Gelfenbaum, Guy; Guerry, Anne; Kim, Choong‐Ki
Abstract Vegetation can protect communities by reducing nearshore wave height and altering sediment transport processes. However, quantitative approaches for evaluating the coastal protection services, or benefits, supplied by vegetation to people in a wide range of coastal environments are lacking. To begin to fill this knowledge gap, we propose an integrated modeling approach for quantifying how vegetation modifies nearshore processes—including the attenuation of wave height, mean and total water level—and reduces shoreline erosion during storms. We apply the model to idealized seagrass‐sand and mangrove‐mud cases, and illustrate its potential by quantifying how those habitats reduce water levels and sediment loss beyond what would be observed in the absence of vegetation. The integrated modeling approach provides an efficient way to quantify the coastal protection services supplied by vegetation and highlights specific research needs for improved representations of the ways in which vegetation modifies wave‐induced processes.